MICROBIAL ACTIVITY AND PHYTOSANITARY CONDITION OF SUNFLOWER CROPS DEPENDING ON THE LEVELS OF BIOLOGIZATION OF CULTIVATION TECHNOLOGY - Lavrenko, Sergiy (Journal of Agricultural Sciences (Belgrade), 2025)
The research was carried out in 2018-2021. The field experiments were conducted in four replications by using the split plot design method. The study was dedicated to evaluation of the following cultivation technology elements: - A - sunflower hybrid: A1 - sunflower hybrid PR64F66 F1 (bred by Pioneer); A2 – sunflower hybrid Tunca F1 (bred by Limagrain); - B - the level of biologization of a cultivation technology: B1 (Traditional); B2 (Biologized І); B3 (Biologized ІІ); B4 (Organic); B5 (Extensive). The research showed that during the growing season, under intensive technology for sunflower cultivation, both the total colonization of the arable soil layer of the research plot and the amount of microflora by certain most principal groups decreased considerably in comparison with the variants where some elements of biologization or their complex application (organic cultivation technology) were implemented – by 6.1–40.9%. Application of modern insecticides of organic origin in the system of sunflower plant protection under biologized and organic cultivation technologies allows controlling a whole array of the most harmful phytophages and is not inferior to synthetic insecticides in effectiveness. The exception is protection of the crop against owlet moth larvae, which, because of their biological and ecological characteristics, require an insecticide preparation to have more systemic properties, which are not characteristic of organic preparations with minor exceptions. There was no residual insecticidal and repellent impact of biological preparations on the major cop pollinators – honey bees (their attendance of flowering inflorescences exceeded this index three times by the variants of intensive and biologized І technologies). Mechanic soil tillage as a method for the crop protection against weeds is an effective alternative to herbicide protection. Application of pre- and post-emergence harrowing with harrows and rotating hoes and inter-row tillage in the system of the crop protection against weeds as a component of biologized and organic technologies for sunflower cultivation is not inferior to application of soil and post-emergence synthetic herbicides in effectiveness, and it is even more effective by the control of the second-third waves of late spring species in the second half of the crop development.
Keywords: sunflower, hybrid, biologization, microorganisms, disease